Comorbidities and risk of mortality in patients with sleep apnea. (4th July 2017) - Chiang, Chi-Lu; Chen, Yung-Tai; Wang, Kang-Ling; Su, Vincent Yi-Fong; Wu, Li-An; Perng, Diahn-Warng; Chang, Shi-Chuan; Chen, Yuh-Min; Chen, Tzeng-Ji; Chou, Kun-Ta
Abstract: Background: A variety of disorders, most notably cardiovascular diseases, was linked to sleep apnea (SA), but their impact on mortality of SA patients had not been systematically investigated. We aimed to develop a composite index based on the comorbidity burden to predict mortality risk. Methods: Using Taiwan National Health Insurance Research Database, 9853 adult SA patients were enrolled and their comorbidity profile at baseline was recorded. The subjects were followed from 1995 till death or the end of 2011. A Cox regression model was used for multivariable adjustment to identify independent predictors for mortality. Results: During an average follow-up period of 5.3 ± 3.1 years, 311 (3.2%) subjects died. SA patients with any comorbidity had a higher risk for death compared to those without comorbidity (HR: 11.01, 95% CI 4.00–30.33, p < 0.001). Age and 10 comorbidities related to increased overall mortality were identified, from which the CoSA (Comorbidities of Sleep Apnea) index was devised. The corresponding hazard ratios for patients with CoSA index scores of 0, 1–3, 4–6, and >6 were 1 (reference), 3.29 (95% CI, 2.04–5.28, p < 0.001), 13.56 (95% CI, 8.63–21.33, p < 0.001), and 38.47 (95% CI, 24.92–59.38, p < 0.001), respectively. Conclusions: Based on the comorbidity burden, we developed an easy-to-use tool to evaluate mortality risk in SA. Key messages: Sleep apnea (SA) is linked to a variety of disorders, particularly cardiovascular diseases. SA patients with any comorbidity may experience a higher risk of death in comparison to those without comorbidity. Comorbidities related to increased mortality are identified and converted into a simple risk indicator, the CoSA (Comorbidities of Sleep Apnea) index scores, which may help to stratify risk of death in daily practice.